"Anybody Can Do It": Aesthetic Empowerment, Urban Citizenship, and the Naturalization of Indonesian Graffiti and Street Art. (December 2013) - LEE, DOREEN
Abstract Based on ethnographic fieldwork in the cities of Jakarta and Yogyakarta, this paper investigates the recent surge in the production and circulation of street art through technology and media in post‐New Order Indonesia. The global style of street art communicates how public space and the street have become emblematic of changing discourses of individual rights, urban aesthetics, and the practice of citizenship in urban Indonesia. While the history of Western graffiti as a form of defacement and resistance continues to exert a powerful hold on the imagination of Indonesian street artists, I argue that the vernacular meaning of street art and graffiti refuses an easy bifurcation of public and private spaces, while blurring the lines between commercial and cultural urban interventions. [Indonesia, street art, graffiti, media, citizenship]